THE EFFECT OF BIOFERTILIZER FORMULATION TO ZOOPLANKTON ABUDANCE AT PANGASIUS SP. POND IN THE PEAT SOIL - Mouch Roddy; Saberina Hasibuan; Syafriadiman Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on April until Juni 2018, in the peat soil of ponds at Petani Nenas Street. Kualu Nenas Village, Kampar district, Riau Province. Observation of zooplankton have been done in the Laboratory of Environment Quality of Aquaqulture, Fisheries and marine faculty. The objective of this research was to know the best doses of biofertilizer formulation to increase zooplankton abundance in the peat soil of ponds and the growth of pangasius sp. The method used was an experiment method with a Completely Randomized Design (CRD), one Factor with five treatments were without giving the biofertilizer (P0), the dose of biofertilizer 700 g/m3 (P1), the dose of biofertilizer 750 g/m3 (P2), the dose of biofertilizer 800 g/m3 (P3), the dose of biofertilizer 850 g/m3(P4). The best treatment of this research was P2 (the dose of biofertilizer 750 g/m3 ). The zooplankton abundance of treatment is 14925 ind/L. absolute grout rate (AGR) pangasius sp. 10,44-22,24 g, specific grout rate (SGR) of pangasius sp. 8,48%-10,86%/day, and the survival rate (SR) 96,50%-98,50%). The water quality parameter in this research are good, especially temperature 27-31 oC, pH 5-6,7, Dissolve oxygen (DO) 2,8-3,6 mg/L, Nitrate concentration 1,91—3,55, concentration of CO2 ……, and orthoposfat concentration 1,41-3,40. Keywords : biofertilizer, zooplankton abundance, peat soil, pangasius sp.